Identifikasi Bakteri Staphylococcus Aureus pada Spons Make-Up di Kalangan Mahasiswa - Putri Maharani; Wiwit Probowati; Widaninggar Rahma Putri (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Makeup sponges are porous cosmetic application tools that are reused and can potentially become a breeding ground for microorganisms if not cleaned regularly. One bacterium that can contaminate makeup sponges is Staphylococcus aureus, which are knew to do play with a role in various skin also soft tissue infections. This reseach was purposelly to identifying the presence of S. aureus towards makeup sponges used by college students. The study employed a quantitative experimental method using purposive sampling on 30 samples of makeup sponges that had been used for at least 1–2 months. Samples were grouped based on washing frequency: frequently washed, rarely washed, and never washed. Bacterial identification was performed via inoculation on Mannitol Salt Agar (MSA) medium, followed by subculturing, Gram staining, catalase testing, and coagulase testing. The results of the study showed colony growth on MSA medium, indicated by a yellow discoloration of the medium. Gram staining revealed coccus-shaped cells arranged in clusters and stained purple, indicating the characteristics of Gram-positive bacteria. The catalase and coagulase tests yielded positive results, confirming the presence of Staphylococcus aureus. Of the 30 samples examined, 7 positive samples were found in the group of sponges that were rarely washed, 6 positive samples in the group that were never washed, and 3 positive samples in the group that were frequently washed. These findings indicate that S. aureus contamination is more common in sponges that are rarely or never washed compared to those cleaned regularly.